Influence of hypercapnic vasodilation on cerebrovascular autoregulation and pial arteriolar bed resistance in piglets - Narayanan, Nithya (American Physiological Society, 2008)
Changes in both pial arteriolar resistance (PAR) and simulated arterial-arteriolar bed resistance (SimR) of a physiologically based biomechanical model of cerebrovascular pressure transmission, the dynamic relationship between arterial blood pressure and intracranial pressure, are used to test the hypothesis that hypercapnia disrupts autoregulatory reactivity. To evaluate pressure reactivity, vasopressin-induced acute hypertension was administered to normocapnic and hypercapnic (N = 12) piglets equipped with closed cranial windows. Pial arteriolar diameters were used to compute arteriolar resistance. Percent change of PAR (%ΔPAR) and percent change of SimR (%ΔSimR) in response to vasopressin-induced acute hypertension were computed and compared. Hypercapnia decreased cerebrovascular resistance. Indicative of active autoregulatory reactivity, vasopressin-induced hypertensive challenge resulted in an increase of both %ΔPAR and %ΔSimR for all normocapnic piglets. The hypercapnic piglets formed two statistically distinct populations. One-half of the hypercapnic piglets demonstrated a measured decrease of both %ΔPAR and %ΔSimR to pressure challenge, indicative of being pressure passive, whereas the other one-half demonstrated an increase in these percentages, indicative of active autoregulation. No other differences in measured variables were detectable between regulating and pressure-passive piglets. Changes in resistance calculated from using the model mirrored those calculated from arteriolar diameter measurements. In conclusion, vasodilation induced by hypercapnia has the potential to disrupt autoregulatory reactivity. Our physiologically based biomechanical model of cerebrovascular pressure transmission accurately estimates the changes in arteriolar resistance during conditions of active and passive cerebrovascular reactivity.